Myology of the species 'Helicops modestus' Günther 1861 (Squamata: Colubridae) - Pavellecini, Enzo Tullio [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Snakes exhibit musculature highly adapted to their lifestyle. Their cephalic muscles allow for a high degree of flexibility and diverse lifestyles, with slight variations among themselves, while the axial musculature is more complex, with elongated, repeated, and interconnected muscles. This musculature is poorly described in the literature, even though the data is of great importance. In this work, I described the axial and cephalic musculature of the species Helicops modestus Günther, 1861, a Brazilian aquatic snake of the Colubridae family common in the Southeast and Midwest regions of Brazil. Nineteen cephalic muscles were described, divided into mandibular adductors, dorsal constrictors, and intermandibular muscles; and seven groups of axial muscles were described, one of which was a previously undescribed muscle. Photographs of the musculature were taken and subsequently edited to facilitate visualization, with later comparison of the results with other Colubridae species. The taxonomic database used for the project was the Reptile Database.

As serpentes apresentam musculatura altamente adaptada ao seu estilo de vida. Seus músculos cefálicos permitem um alto grau de flexibilidade e diversos estilos de vida, com variações leves entre si, enquanto a musculatura axial é mais complexa, com músculos alongados, repetidos e interligados. Tal musculatura é pouco descrita na literatura, mesmo que sejam dados de grande importância. Neste trabalho, foi feita a descrição da musculatura axial e cefálica da espécie Helicops modestus Günther, 1861, uma serpente aquática brasileira da família Colubridae comum no Sudeste e Centro-Oeste. Foram descritos 19 músculos cefálicos, divididos em adutores da mandíbula, constritores dorsais e intermandibulares; e foram descritos 7 grupos de músculos axiais, um deles sendo um músculo não descrito. Foram tiradas fotos da musculatura e sua posterior edição para facilitar a visualização da musculatura, com a posterior comparação dos resultados com outras espécies de Colubridae. O banco de dados taxonômico utilizado para o projeto foi o Reptile Database.
Miologia da espécie 'Helicops modestus' Günther 1861 (Squamata: Colubridae)
Keywords: Serpentes; Músculos; Colubridae; Helicops; Snakes; Muscles; Colubridae; Helicops